Quality indicators for the management of muscle-invasive bladder cancer in the perioperative setting of radical cystectomy: a narrative review - König, Frederik; Pradere, Benjamin; Grossmann, Nico C; Quhal, Fahad; Rajwa, Pawel; Laukhtina, Ekaterina; Mori, Keiichiro; Katayama, Satoshi; Yanagisawa, Takafumi; Mostafai, Hadi; Motlagh, Reza Sari; Aydh, Abdulmajeed; et al. (Translational cancer research, 2022)
BACKGROUND AND OBJECTIVE: Identifying evidence-based and measurable quality-of-care indicators is crucial for optimal management of patients requiring radical cystectomy (RC) for muscle-invasive bladder cancer (MIBC). RC with urinary diversion and lymphadenectomy is the standard treatment for patients with MIBC. Preoperatively, neoadjuvant chemotherapy (NAC) with cisplatin-based combinations improves survival outcomes and is the recommended standard of care for eligible patients. Intraoperatively, lymph node dissection (LND) by, at least, following a standard pelvic lymph node template improves overall- and recurrence-free survival and allows for accurate tumour staging. Avoiding positive soft tissue surgical margins (STSM) should be a main target intraoperatively since they are almost universally associated with mortality. Implementing enhanced recovery after surgery (ERAS) programs can reduce lengths of hospital stay (LOS) and postoperative complication rates without increasing readmission rates after RC. Moreover, several studies have shown that smoking negatively affects local and systemic treatment outcomes in bladder cancer (BC) patients. Therefore, smoking cessation counselling for smokers should be an essential part of bladder cancer management regardless of the disease state. METHODS: We performed a comprehensive, non-systematic review of the latest literature to define indicators representing the best evidence available for optimal care of MIBC patients treated with RC. KEY CONTENT AND FINDINGS: In this review, we propose five major quality indicators that are easily implementable for optimized management of MIBC patients treated with RC, including: usage of cisplatin-based NAC in eligible patients, ensurance of negative STSM, performance of (at least) a standard pelvic template LND, implementation of ERAS strategies, and professional smoking cessation counselling. CONCLUSIONS: Optimal management of MIBC needs to be framed by evidence-based, reproducible, and measurable quality indicators that will allow for guidance and comparative effectiveness assessment of clinical practices; adherence to them is likely to improve patients' prognoses by a tensible margin. For the treatment of MIBC patients with RC, we identified five essential quality indicators. KEYWORDS: Assessment; bladder cancer (BC); muscle-invasive bladder cancer (MIBC); cystectomy; radical cystectomy (RC); quality.